Synergetic effect of ZnO/NiO nanocomposite on the enhancement of photocatalytic degradation efficiency of dyes molecules - Iasya, Yurin Karunia Apsha Albaina; Khoerunnisa, Fitri; Dwi, Sadina Sahitya; Putri, Restiani Alia; Nurhayati, Mita; Arrozi , Ubed Sonai Fahruddin; Permana, Yessi; Handayani, Murni; Astuti, Wijayanti Dwi; Da, Oh Wen; Irnanda, Istifhamy (Communications in Science and Technology, 2025)
The discharge of organic dyes into water systems poses severe risks to human health and aquatic ecosystems. A remarkable technique that is increasingly recognized for dyes degradation is photocatalysis. This work aims to investigate the role of zinc oxide/nickel oxide (ZnO/NiO) nanocomposites in enhancing photocatalytic degradation efficiency of dyes molecules. The nanocomposites were prepared using a simple ultrasonication technique and analyzed through X-ray diffraction (XRD), scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). The XRD pattern of the ZnO/NiO nanocomposites exhibited characteristic peaks aligned with the ZnO and NiO phases, referring to JCPDS standards. The SEM images of nanocomposites featured the rod and irregular flake-like structures with the average size of 80 nm. The nanocomposites showed the highest dye photodegradation efficiency (RB 93.65% and MO 94.82%) in view of a larger semicircular diameter and lowest band gap energy as verified by Nyquist plot and DFT calculation. These results emphasized the synergistic effect of ZnO/NiO nanocomposites in promoting dye photocatalytic degradation.